Multiple models guide strategies for agricultural nutrient reductions. Issue 3 (April 2017) - Scavia, Donald; Kalcic, Margaret; Muenich, Rebecca Logsdon; Read, Jennifer; Aloysius, Noel; Bertani, Isabella; Boles, Chelsie; Confesor, Remegio; DePinto, Joseph; Gildow, Marie; Martin, Jay; Redder, Todd; et al.
Abstract : In response to degraded water quality, federal policy makers in the US and Canada called for a 40% reduction in phosphorus (P) loads to Lake Erie, and state and provincial policy makers in the Great Lakes region set a load‐reduction target for the year 2025. Here, we configured five separate SWAT (US Department of Agriculture's Soil and Water Assessment Tool) models to assess load reduction strategies for the agriculturally dominated Maumee River watershed, the largest P source contributing to toxic algal blooms in Lake Erie. Although several potential pathways may achieve the target loads, our results show that any successful pathway will require large‐scale implementation of multiple practices. For example, one successful pathway involved targeting 50% of row cropland that has the highest P loss in the watershed with a combination of three practices: subsurface application of P fertilizers, planting cereal rye as a winter cover crop, and installing buffer strips. Achieving these levels of implementation will require local, state/provincial, and federal agencies to collaborate with the private sector to set shared implementation goals and to demand innovation and honest assessments of water quality‐related programs, policies, and partnerships.